Penggunaan Sistem Paylatter dalam Perspektif Hadis - Hifzilla Azzahro Rivera; Rahima Sikumbang (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research explores the use of the Paylatter system (instalmental payments) from a hadith perspective in an effort to understand its relevance to Islamic religious principles. The Paylatter system is a payment method that allows buyers to pay for goods or services in several installments, which is developing rapidly in the modern era. The aim of this research is to find out explanations of the hadiths that explain the paylatter system and to find out how to thematically understand the hadiths that explain the paylatter system. The research method used in this study is literature study, which involves searching, analyzing and synthesizing scientific literature relevant to the topic. The results of this research reveal various views from scholars and researchers in existing literature. This study discusses various arguments that have emerged in the literature about whether the use of paylatter systems is in accordance with the principles of hadith and Islamic ethics. From the research results, it is known that there are elements of benefit in the form of processes and procedures that are fast and more useful, have varying time periods, and also have various attractive promotions. As for the detrimental elements, there are additional fees and interest, causing users to feel addicted and losing money, and can tarnish credit reputation and tarnish BI checking. The paylatter system uses a qardh contract which is permitted in Islam if it meets the pillars and conditions. Some scholars allow paylatter as long as there are no additional late fees, others prohibit it because there are many disadvantages.